Diagnóstico e avaliação da influência de contaminantes selvagens durante etapas do processo produtivo do etanol - Santos, Camila Oliveira dos (2021)
Ethanol production represents an important share in the national economy. With the use of sugarcane as a raw material, Brazil is positioned as the second largest producer in the world. Although the ethanol production process is well established, many factors contribute to its efficiency, such as the quality of the raw material, process conditions and microbial contaminants. Sugarcane juice must is a very complex substrate and allows the development of other yeasts of the genus Saccharomyces and non-Saccharomyces, so the microbial population during industrial fermentations can be quite dynamic, and the yeast can be completely replaced in wild yeast process. In view of this, this study proposes to study the fermentative characteristics of contaminating yeast strains isolated from six stages of the production process of an ethanol producing plant in the state of Goiás and the implications that these yeasts could have on the final ethanol yield. The samples were collected from the final melasse, must, concentrated broth, decanted broth, yeast from the vat and fermented wine. From the colonies isolated from the fermented wine, a wild yeast strain with rough appearance and irregular edges was found at a contamination level of 77.4 % of the sample. Thus, fermentative tests were carried out in triplicates with synthetic must of sugar cane with 120 g.L-1 of sugars with a period of 72 hours of fermentation. Firstly, the performance of fermented wine isolated yeast (LFS) was evaluated in comparison with the industrial strains Saccharomyces cerevisiae BG-1, CAT-1, FT-858L and PE-2. LFS obtained lower values in final ethanol concentration, productivity and fermentative efficiency compared to industrial strains. However, in LFS mixed culture fermentative tests at contamination levels of 2, 10, 20 and 30 % with strains BG-1, CAT-1, FT-858L and PE-2, the LFS showed higher levels of final contamination than the initial, thus showing the competence of industrial yeasts over wild yeast, in these same conditions with reuse of the inoculum, the LFS was reduced from 30 % to 0.2 % at the end of 10 consecutive fermentations. In this study, the isolated LFS yeast became more dominant in mixed culture fermentations with the PE-2 strain and in must with calcium oxide additions, between concentrations of 0.05 g.L-1 and 0.30 gL-1 of CaO the results showed a significant drop in fermentation efficiency. The wort of the plant presented an additional calcium concentration of 0.09 g.L-1 after the liming treatment, this concentration is worrying considering that in the tests with the concentration of 0.10 gL-1 of CaO, it was observed that the speed growth rate of LFS was greater than that of the PE-2 strain, possibly this was the condition that favored the critical contamination situation observed in the plant samples, and may mention the possibility of replacing calcium oxide in liming treatment or alternatives that minimize the presence of Ca2+ ions in the must so that it does not favor the development of flocculating yeasts.